2017
DOI: 10.18632/oncotarget.21949
|View full text |Cite
|
Sign up to set email alerts
|

Tomentodione M sensitizes multidrug resistant cancer cells by decreasing P-glycoprotein via inhibition of p38 MAPK signaling

Abstract: In this study, we investigated the mechanism by which tomentodione M (TTM), a novel natural syncarpic acid-conjugated monoterpene, reversed multi-drug resistance (MDR) in cancer cells. TTM increased the cytotoxicity of chemotherapeutic drugs such as docetaxel and doxorubicin in MCF-7/MDR and K562/MDR cells in a dose- and time-dependent manner. TTM reduced colony formation and enhanced apoptosis in docetaxel-treated MCF-7/MDR and K562/MDR cells, and it enhanced intracellular accumulation of doxorubicin and rhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Recently, Zhou and colleagues have found that tomentodione M, a novel meroterpenoid isolated from R. tomentosa leaves, increased the cytotoxicity of chemotherapeutic drugs such as docetaxel and doxorubicin in human breast cancer cells/reversed multidrug resistance (MCF-7/MDR cells) and human immortalized myelogenous leukemia cells/reversed multidrug resistance (K562/MDR cells). Additionally, the anticancer activity of tomentodione M was observed due to reducing colony formation, enhancing apoptosis in docetaxel-treated MCF-7/MDR and K562/MDR cells, increasing intracellular accumulation of doxorubicin and rhodamine 123 in MDR cancer cells, and down-regulating P-gp mRNA and protein expression [96]. Thus, tomentodione M may be a useful anticancer natural product.…”
Section: Pharmaceutical Propertiesmentioning
confidence: 99%
“…Recently, Zhou and colleagues have found that tomentodione M, a novel meroterpenoid isolated from R. tomentosa leaves, increased the cytotoxicity of chemotherapeutic drugs such as docetaxel and doxorubicin in human breast cancer cells/reversed multidrug resistance (MCF-7/MDR cells) and human immortalized myelogenous leukemia cells/reversed multidrug resistance (K562/MDR cells). Additionally, the anticancer activity of tomentodione M was observed due to reducing colony formation, enhancing apoptosis in docetaxel-treated MCF-7/MDR and K562/MDR cells, increasing intracellular accumulation of doxorubicin and rhodamine 123 in MDR cancer cells, and down-regulating P-gp mRNA and protein expression [96]. Thus, tomentodione M may be a useful anticancer natural product.…”
Section: Pharmaceutical Propertiesmentioning
confidence: 99%
“…Novel pharmacological approaches to overcome drug resistance in cancer have been established in recent decades. Targeting active drug transporters such as MDR1, for example, can resensitize drug-resistant tumor cells to anti-cancer drugs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…6) ABCB1 is a target of the Ras/Raf signaling pathway, suppression of p38, ERK or JNK pathways enhanced sensitivity to chemotherapeutic drugs in multidrug resistant tumor cells. [7][8][9][10] Paris polyphylla var. yunnanensis (Franch.)…”
Section: Introductionmentioning
confidence: 99%